Human trafficking, a shadow of migration: Evidence from Germany - Seo-Young Cho (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper empirically analyzes the relationship between migration and human trafficking inflows into Germany during the period between 2001 and 2010. My results suggest that migrant networks, measured by migrant stocks from a specific source country, have a causal linkage with the illicit, exploitative form of migration - human trafficking - from that respective country. However, the network effect varies across different income levels of source countries. The significant, positive effect of migrant networks on human trafficking decreases as the income level increases, and furthermore the effect is insignificant for high income countries.
Keywords: F22; J23; J61; 330; Human trafficking; Migration; Network effects